Transfer of Learning in Work-Based Learning Approach for Bachelor of Technology Program - Amirul Afiq Ahmad Majdi; Yunus, Faizal Amin Nur; Mohd Bekri Rahim; Khairul Anuar Abd Rahman; Nizamuddin Razali (Online Journal for TVET Practitioners, 2026)
This study examines the transfer of learning in the Work-Based Learning (WBL) approach among Bachelor of Technology (BTech) program graduates at Universiti Tun Hussein Onn Malaysia (UTHM). This study examines the relationship between trainee characteristics, training design, work environment, and virtual learning space with the effectiveness of learning transfer. Data were collected using a structured questionnaire and statistically analyzed. The findings showed that the level of learning transfer was at a moderate level (Mean = 3.584), with virtual learning space recording the highest mean (Mean = 3.764), followed by trainee characteristics (Mean = 3.538), training design (Mean = 3.514), and work environment (Mean = 3.494). These results emphasize the importance of digital interaction and social engagement in facilitating learning transfer. This study recommends improvements in the design of WBL programs as well as strengthening university-industry collaboration to increase the employability of graduates.